THE INFLUENCE OF BRAND EXPERIENCE AND EMOTIONAL ATTACHMENT ON BRAND TRUST AND BRAND LOYALTY CHURCH MAWAR SHARON, WEST SURABAYA - Harjanto, Hans Christian; Ellitan, Lena; Muljani, Ninuk (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2021)
This study aims to analyze the effect of brand experience and emotional attachment on brand trust and brand loyalty in Mawar Sharon Church in West Surabaya. Currently, the level of membership, attendance, and participation in Christian churches has decreased. The data analysis technique used is SEM-PLS analysis with the SmartPLS program. The research results prove that brand experience has a significant effect on emotional attachment and brand loyalty, but insignificant on brand trust. Emotional attachment has a significant effect on brand trust and brand loyalty. Brand trust has a significant influence on brand loyalty. The role of emotional attachment is also significant as a mediator for brand experience on brand trust and brand loyalty. The role of brand trust as a mediator for brand experience and brand loyalty is insignificant. Suggestions from research for the Mawar Sharon Church in West Surabaya are to take a personal approach to the congregation and create programs, so that there is a personal bond between the congregation and the Mawar Sharon Church in West Surabaya and increase the congregation's trust and attachment to the church. but insignificant on brand trust.